Spectrum of Dental Phenotypes in Nonsyndromic Orofacial Clefting. (July 2015) - Howe, B.J.; Cooper, M.E.; Vieira, A.R.; Weinberg, S.M.; Resick, J.M.; Nidey, N.L.; Wehby, G.L.; Marazita, M.L.; Moreno Uribe, L.M.
Children with oral clefts show a wide range of dental anomalies, adding complexity to understanding the phenotypic spectrum of orofacial clefting. The evidence is mixed, however, on whether the prevalence of dental anomalies is elevated in unaffected relatives and is mostly based on small samples. In the largest international cohort to date of children with nonsyndromic clefts, their relatives, and controls, this study characterizes the spectrum of cleft-related dental anomalies and evaluates whether families with clefting have a significantly higher risk for such anomalies compared with the general population. A total of 3, 811 individuals were included: 660 cases with clefts, 1, 922 unaffected relatives, and 1, 229 controls. Dental anomalies were identified from in-person dental exams or intraoral photographs, and case-control differences were tested using χ 2 statistics. Cases had higher rates of dental anomalies in the maxillary arch than did controls for primary (21% vs. 4%, P = 3 × 10 −8 ) and permanent dentitions (51% vs. 8%, P = 4 × 10 −62 ) but not in the mandible. Dental anomalies were more prevalent in cleft lip with cleft palate than other cleft types. More anomalies were seen in the ipsilateral side of the cleft. Agenesis and tooth displacements were the most common dental anomalies found in case probands for primary and permanent dentitions. Compared with controls, unaffected siblings (10% vs. 2%, P = 0.003) and parents (13% vs. 7%, P = 0.001) showed a trend for increased anomalies of the maxillary permanent dentition. Yet, these differences were nonsignificant after multiple-testing correction, suggesting genetic heterogeneity in some families carrying susceptibility to both overt clefts and dental anomalies. Collectively, the findings suggest that most affected families do not have higher genetic risk for dental anomalies than the general population and that the higher prevalence of anomalies in cases is primarily a physical consequence of the cleft and surgical interventions.